UVB phototherapy for pityriasis rosea: A bilateral comparison study - Vichit Leenutaphong (2018)
Background: Pityriasis rosea is a common self-limiting disease. UV light has been mentioned as helpful, but only a few studies substantiate this possibility. Objective: Our purpose was to evaluate the clinical efficacy of UVB phototherapy in pityriasis rosea and the course of the disease after treatment. Methods: Seventeen patients with extensive pityriasis rosea were treated with unilateral UVB phototherapy in a bilateral comparison study. One joule of UVA was used as a "placebo" on the untreated side. The treatments were given five times per week for 2 weeks. The rate of clearing was monitored by estimation of the severity score. Results: Ten daily erythemogenic exposures of UVB resulted in substantially decreased severity of disease, greater than that on the untreated side in 15 of 17 patients. The overall reduction of severity score showed a significant difference after the third treatment; the UVB irradiation was superior. However, during the follow-up period the two sides were indistinguishable in regard to severity score (p = 0.6784). No significant difference in pruritus was noted between the two sides (p > 0.1638). The duration of disease did not relate to the success of UVB phototherapy. Conclusion: During the treatment period UVB phototherapy resulted in decreased severity of disease. However, the itching and the course of the disease were unchanged. © 1995.